Mueller manoeuvre increases the mitral‐to‐aortic velocity–time integral ratio, a mitral regurgitant index, in patients with dilated cardiomyopathy - Juha Virolainen; Markku Ventilä; Markku Kupari (Clinical Physiology and Functional Imaging, 2026)
Abstract A reduction of intrathoracic pressure during the Mueller manoeuvre (MM) has been shown to decrease left ventricular (LV) forward stroke volume in patients with systolic heart failure. To assess the underlying mechanisms, we analyzed MM‐induced changes in LV inflow and outflow dynamics in 13 healthy individuals (mean age 42 y, 8 men) and in 13 patients with dilated cardiomyopathy (DCM) (mean age 44 y, 8 men) having LV ejection fraction 10 s. Doppler echocardiography was used to record systolic and diastolic flow velocities at the aortic and mitral valve annulus, respectively, during quiet respiration and the MM. The respective flow velocity‐time integrals (VTI) were measured. Compared with control subjects, patients with DCM had a larger MM‐induced decrease in the aortic VTI (−4.2 ± 0.3 vs. −1.6 ± 0.5 cm; p < 0.001) combined with a tendency to a smaller decrease in the mitral VTI (−1.4 ± 0.5 vs. –2.2 ± 0.3 cm; p = 0.070). The mitral‐to‐aortic VTI ratio, an indirect mitral regurgitant index, increased in DCM from 0.78 ± 0.04 to 1.03 ± 0.08 ( p = 0.006) but decreased in the control group from 0.70 ± 0.03 to 0.61 ± 0.03 ( p = 0.025). The group x MM interaction was statistically highly significant ( F = 16.8, p < 0.001). We conclude that, in DCM‐related heart failure, a reduction of intrathoracic pressure during the MM increases the mitral‐to‐aortic VTI ratio suggesting appearance of functional mitral regurgitation.